1987
DOI: 10.1177/002076408703300404
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Usa and New Zealand Patients' Requests and Clinicians Understanding of Patients' Requests

Abstract: This study compares USA and New Zealand psychiatric patients' requests at the initial psychiatric interview and examines clinician's accuracy in estimating patients' treatment request preferences. Eighty-five of the 146 consecutive nonacute patients to the psychiatric unit of a public New Zealand hospital completed a 14-item Patient Request Form before their initial interview and their clinician completed an equivalent form at the end of the interview. Patients' treatment request preferences were similar in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…It appears that the differences between the two samples may be related to a limited band of expectations which relate to how active or passive the client expects to be, and how much they expect to talk about difficult topics. Finding similarities in the expectations of the two samples is consistent with previous research which found correlations as high as r=.8~, p < .O1 between USA and NZ psychiatric outpatients initial treatment request preferences (Deane, 1987).…”
Section: Discussionsupporting
confidence: 90%
“…It appears that the differences between the two samples may be related to a limited band of expectations which relate to how active or passive the client expects to be, and how much they expect to talk about difficult topics. Finding similarities in the expectations of the two samples is consistent with previous research which found correlations as high as r=.8~, p < .O1 between USA and NZ psychiatric outpatients initial treatment request preferences (Deane, 1987).…”
Section: Discussionsupporting
confidence: 90%
“…Why was emotion management related to help-seeking but not emotion perception? One of the major reasons people seek help is to put things into perspective and clarify how they are feeling (Deane, 1987). People high in emotion perception may already have a good understanding of what they are feeling and not believe they need to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…Deane (1987) found that of 14 request categories the five ranked highest by patients (in order of preference) were: 1. &dquo;Clarification&dquo; -To get help to put things into perspective; 2.…”
mentioning
confidence: 99%